PENGARUH PENAMBAHAN AIR REBUSAN KULIT JENGKOL (archidendron pauciflorum) KEDALAM AIR MINUM TERHADAP PERFORMA KARKAS BROILER - Syintia Dwi Agustina; Sadjadi Sadjadi; Ririn Novita (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
This study aims to determine the use of boiled water of jengkol (Archidendron pauciflorum) peel in drinking water on broiler carcass performance. The study used 96 DOC broilers of the type MB 202 PLATINUM with a study duration of 4 weeks. The research method used is an experimental method using a completely randomized design (CRD) with 6 treatments, namely P0: Control (Drinking water without boiled jengkol peel waste), P1: 2% (2ml jengkol peel decoction/100ml drinking water), P2: 4 % (4 ml of boiled jengkol peel/100 ml of drinking water), P3: 6% (6 ml of boiled jengkol peel/100 ml of drinking water), P4: 8% (8 ml of boiled jengkol peel/100 ml of drinking water), P5: 10% (10 ml of boiled peel) jengkol/100 ml of drinking water) then each treatment was repeated 4 times. The parameters measured were: live weight (g/head), carcass weight (g/head), and abdominal fat weight (g/head). The results of the analysis of diversity showed that the administration of boiled water jengkol peelÂ in drinking water had a significant effect (P<0.05) on carcass weight and abdominal fat weight, and was only able to maintain the same live weight as the control. Based on the results of the study, it can be concluded that the best treatment of jengkol peel boiled water in drinking water is P4 8% treatment (8ml jengkol peel stew/100ml drinking water) with the acquisition of live weight 1089.50 g/head, carcass weight 883.50 g/head, and abdominal fat 9.98 g/head. Keywords: Broiler, Carcass Quality, Jengkol Peel Decoction